The contribution of pre-existing spinal pseudarthrosis to the surgical correction for thoracolumbar kyphosis secondary to ankylosing spondylitis. (December 2020) - Qiao, Mu; Qian, Bang-ping; Qiu, Yong; Zhao, Shi-zhou; Huang, Ji-chen; Wang, Bin
Highlights: PSO away from pseudarthrosis was a feasible method for AS-related kyphosis. GK correction consisted of three parts: OV, pseudarthrosis and interbody disc space. Contribution of pseudarthrosis should be considered for surgical decision-making. Abstract: The correction of global kyphosis (GK) for ankylosing spondylitis (AS) patients with pre-existing pseudarthrosis were frequently over 45°. Mismatch between kyphosis correction of GK and pedicle subtraction osteotomy (PSO) may be ascribed to contribution of pseudarthrosis. The aim of the present study was to evaluate surgical outcomes of PSO away from the level of pseudarthrosis and to elucidate the contribution of pre-existing spinal pseudarthrosis in surgical correction of thoracolumbar kyphosis caused by AS. Eighteen AS patients with pre-existing pseudarthrosis were included. PSO outside the level of pseudarthrosis were performed for all the patients. The average follow-up period were 29 months. Radiographs were analyzed for correction and complications. Significant improvement in all sagittal parameters were found postoperatively without obvious correction loss at the final follow-up. Local kyphosis (LK) improved from 23.88° preoperatively to 12.67° postoperatively with a mean correction of 11.47°. Average correction of per PSO segment, GK and sum of disc wedging within fused region (SDW) were 33.53°, 49.27° and 4.00°, respectively. PSO away from the level of pseudarthrosis, but with posterior instrumentation crossing it was a feasible method and was able to maintain sustained surgical outcomes. Regarding GK correction, PSO accounted for 68.1% while pre-existing pseudarthrosis provided 23.3%, which resulted from anterior column opening postoperatively. Thus, extra kyphosis correction attributed to pre-existing pseudarthrosis should be considered for surgical-decision making to prevent overcorrection.